1996
DOI: 10.1073/pnas.93.12.5709
|View full text |Cite
|
Sign up to set email alerts
|

A gain-of-function of an amyotrophic lateral sclerosis-associated Cu,Zn-superoxide dismutase mutant: An enhancement of free radical formation due to a decrease in Km for hydrogen peroxide.

Abstract: Cu,Zn-superoxide dismutase (SOD) is known to be a locus of mutation in familial amyotrophic lateral sclerosis (FALS). Transgenic mice that express a mutant Cu,Zn-SOD, Because the levels of total Cu,Zn-SOD activity in these transgenic mice are greater than normal, the plausible interpretation of the ALS symptoms in these mice is that the mutant is in some way cytotoxic. The nature of this cytotoxic gain-offunction of the FALS mutants is yet to be identified.In addition to the usual superoxide dismutation acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
232
1
2

Year Published

1997
1997
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(245 citation statements)
references
References 29 publications
10
232
1
2
Order By: Relevance
“…In some familial ALS cases, mutations to the C u binding site of CdZn superoxide dismutase (SOD; superoxide oxidoreductase, EC 1.15.1 . l ) may increase the level of Cu-associated toxicity in motor neurons (Wiedau-Pazos et al, 1996;Yim et al, 1996;Ghadge et al, 1997;Zu et al, 1997).…”
mentioning
confidence: 99%
“…In some familial ALS cases, mutations to the C u binding site of CdZn superoxide dismutase (SOD; superoxide oxidoreductase, EC 1.15.1 . l ) may increase the level of Cu-associated toxicity in motor neurons (Wiedau-Pazos et al, 1996;Yim et al, 1996;Ghadge et al, 1997;Zu et al, 1997).…”
mentioning
confidence: 99%
“…In the presence of H202 and radical scavengers, especially with anionic character, both free 9 radicals and scavenger-derived radicals are produced (15,16). We also found that the free radical-generating function of several FALS-associated Cu,Zn-SOD mutants is enhanced relative to that of the wild-type enzyme, while the dismutation activities remain unchanged (17,18).…”
mentioning
confidence: 64%
“…In the presence of H202 and radical scavengers, especially with anionic character, both free 9 radicals and scavenger-derived radicals are produced (15, 16). We also found that the free radical-generating function of several FALS-associated Cu,Zn-SOD mutants is enhanced relative to that of the wild-type enzyme, while the dismutation activities remain unchanged (17,18).To monitor the production of free radicals, two spin traps, 5,5-dimethyl-l-pyrroline N-oxide (DMPO) and Ntert-butyl-c~-phenylnitrone (PBN), were used in our studies (15) to convert transient free radicals to stable free radicals adducts according to the following reactions:The nature of the trapped free radical was identified by EPR spectroscopy. When O2-" (dissolved KO 2 in dried dimethylsulfoxide) was added to the NaHCOJCO 2 buffer at pH 7.6 containing 100 mM DMPO, EPR OH adducts.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…The oxidative damage to proteins, lipids and DNA are all detectable and have been shown to vary among individuals, species and phylogenetic groups and to increase with age. Damage inflicted by ROS is believed to be implicated as the cause of a number of degenerative diseases including Parkinson's disease, amyotrophic lateral sclerosis (Lou Gehrig's disease) and others (Yim et al, 1996;Wallace, 1996;Simonian and Coyle, 1996). Though the activity in antioxidant enzymes may not correspond to its predicted role in aging (Matsuo et al, 1992), the "free radical" hypothesis clearly has a reasonable basis in documentation of the disastrous effects of oxygen use .…”
Section: Introductionmentioning
confidence: 99%